Corporate governance and the African business context: the case of Nigeria - Letza, Steve (Economics and Business Review, 2017)
A robust institutional framework is essential to enable fi rms to function efficiently. The aspect of corporate governance investigated in this paper is the legal andsocietal principles and process which form the business context within which firmsoperate. The paper explores the challenges to firms trading in Africa arising from culturaldynamics peculiar to the continent and further explores the historical reasonsfor the present cultural context to business in Africa. Nigeria is presented as a specialcase, perhaps even an extreme case, of the challenges to corporate governance inAfrica since it is perceived by many to be one of the weaker environments given itsperceived levels of corruption. The paper concludes with an assessment of the likelihoodof African states successfully tackling corruption in the future as the current approachesunfold over the coming years.